Constrained Large-Eddy Simulation of Compressible Flow Past a Circular Cylinder (Communications in Computational Physics, 2018)
Compressible flow past a circular cylinder at an inflow Reynolds numberof 2×105 is numerically investigated by using a constrained large-eddy simulation(CLES) technique. Numerical simulation with adiabatic wall boundary condition andat a free-stream Mach number of 0.75 is conducted to validate and verify the performance of the present CLES method in predicting separated flows. Some typical andcharacteristic physical quantities, such as the drag coefficient, the root-mean-square liftfluctuations, the Strouhal number, the pressure and skin friction distributions aroundthe cylinder, etc. are calculated and compared with previously reported experimentaldata, finer-grid large-eddy simulation (LES) data and those obtained in the present LESand detached-eddy simulation (DES) on coarse grids. It turns out that CLES is superiorto DES in predicting such separated flow and that CLES can mimic the intricate shockwave dynamics quite well. Then, the effects of Mach number on the flow patterns andparameters such as the pressure, skin friction and drag coefficients, and the cylindersurface temperature are studied, with Mach number varying from 0.1 to 0.95. Nonmonotonic behaviors of the pressure and skin friction distributions are observed withincreasing Mach number and the minimum mean separation angle occurs at a subcritical Mach number of between 0.3 and 0.5. Additionally, the wall temperature effects onthe thermodynamic and aerodynamic quantities are explored in a series of simulationsusing isothermal wall boundary conditions at three different wall temperatures. It isfound that the flow separates earlier from the cylinder surface with a longer recirculation length in the wake and a higher pressure coefficient at the rear stagnation point forhigher wall temperature. Moreover, the influences of different thermal wall boundaryconditions on the flow field are gradually magnified from the front stagnation point tothe rear stagnation point. It is inferred that the CLES approach in its current version is a useful and effective tool for simulating wall-bounded compressible turbulent flowswith massive separations.